Arts and Culture focus Schools in the Western Cape: Insights into a music Program in low-income secondary schools - Johnson, Ross (School of Education, 2024)
This dissertation offers insights into an Arts & Culture Focus School music programme that was implemented at 10 low-income secondary schools in the Western Cape from 2005 to 2014. The motivation behind the initiative was to try to introduce and develop different kinds of skills and abilities at these schools. This was seen as a way of utilising the greater provision of vocational education in schools to develop human capital that improves the provincial economy. The Western Cape Education Department established the Focus Schools programme in the province in 2005 solely at low-income secondary schools. The pilot programme was deemed a provincial success and later came to serve as a key model that informed the introduction of the three-stream education model by the national Department of Basic Education in 2014. Arguably, the Focus School programme served as a prototype for the kinds of provision that would manifest itself as the occupational learning stream within the new Three Stream Model (the others being academic and vocational). For the dissertation, the study conducted semi-structured qualitative interviews at three of the 10 Arts and Culture Focus Schools in the province. Eight participants, including three headmasters and two members of the Western Cape Education Department, were interviewed. The participants provided a variety of insights on the Focus Schools model. The dissertation utilised the theoretical lens of Critical, Cultural, Political, Economy in Education to analyse the responses of the participants and to make sense of what they shared. This was done in the context of a neoliberal provincial mindset that viewed all learners as forms of human capital that needed to serve the South African and provincial capitalist economy. The dissertation suggests that while the Focus Schools programme was generally poorly resourced and offered little support for both Arts and Culture (especially music) teachers and learners in the programme in the period 2005-2014, the initiative did invariably lead to greater learner participation and performance at the designated schools. The programme continues to offer long-term benefits to the schools with the kinds of curricula and foci that the initiative provided. In particular, it can be said that the Focus Schools programme increased music education opportunities for learners in low-income secondary schools, which has helped embed and recognise the importance of music education within the larger national education and training landscape